APLIKASI LAYANAN JAHIT MENGGUNAKAN FRAMEWORK REACT NATIVE - Siregar, Elisa Basaria; Fauzi, Rahmat (LPPM Universitas Putera Batam, 2021)
Human lifes inseparable from primary needs, namely clothing, food and boards. Clothing is a basic human need for clothing used to protect the human body. Current development making clothes can not only protect the human body but also develop into fashion with various models which of course require tailoring services to sew clothes according to customer needs. The process of the customer getting the desired tailor service when this is still using word of mouth or ordering services atau sew on one tailor who has subscribed. Batam city has many services home tailors and customers who still use these methods and less efficient for a tailor and a prospect. This study aims to build a sewing service application which supports the provision of home sewing services and customers. Development this application uses the waterfall model and testing The application uses the black box testing method. Programming language that used is PHP and Javascript using the react native framework as framework and MySQL as database. This application is expected to make it easier for a customer and tailor to be able to connect with each other using the application.